PEMBELAJARAN KEWIRAUSAHAAN DAN MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) : STUDI KASUS DI JURUSAN TEKNIK MESIN POLITEKNIK NEGERI JAKARTA - Tri Widjatmaka; Rahma Nur Praptiwi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Entrepreneurship activities are one of the programs in the Merdeka Belajar Kampus Merdeka (KW-MBKM). Entrepreneurship has been taught as a subject at the Department of Mechanical Engineering at the Jakarta State Polytechnic (JTM-PNJ). This study aims to determine the implementation of entrepreneurship learning that has been implemented by JTM-PNJ as a basis for developing entrepreneurial learning and supporting the implementation of MBKM. As an indicator of development are the provisions set by the Ministry of Education and Culture regarding KW-MBKM. The research was carried out at JTM-PNJ for the academic year 2020/2021. The data sources of this research are JTM-PNJ students who have received entrepreneurship learning. Methods of data collection is done by using the method of questionnaires and documentation. The data analysis technique used is descriptive analysis, both quantitatively and qualitatively. The results of the study show that: [1] the effectiveness of entrepreneurship learning based on entrepreneurial values ​​is good; [2] SCL learning has been carried out even though it is not optimal due to the lack of practical material/direct experience; [3] the implementation of entrepreneurship learning has not been managed at the university level (PNJ); [4] collaboration between several courses to support entrepreneurial learning has not been carried out; [5] the use of rubrics in the assessment has not been carried out; [6] collaboration with the business incubation unit in learning has not been intensive; [7] collaboration with the business world in entrepreneurship learning is still lacking; [8] the effect of the learning process is relatively small on the effectiveness of entrepreneurship learning.